2015
DOI: 10.3390/jmse3030720
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and Sediment Modelling within a Macro Tidal Estuary: Port Curtis Estuary, Australia

Abstract: An understanding of sediment transport processes and resultant concentration dynamics in estuaries is of great importance to engineering design awareness and the management of these environments. Predictive modelling approaches provide an opportunity to investigate and address potential system responses to nominated events, changes, or conditions of interest, often on high temporal and spatial resolution scales. In this study, a three-dimensional hydrodynamic model and wave model were validated and applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
(62 reference statements)
1
10
0
Order By: Relevance
“…For example, in the outer seaward Wild Cattle Channel the data indicate that the sediment has a marine rather than catchment derivation, with 7 Be activities equally low in dry and post wet conditions and less depleted δ 13 C. Wild Cattle Channel also had a similar REE composition to sediments from offshore of the Rodds Peninsula, a site chosen as indicative of longshore drift. Such a finding is supported by previous hydrodynamic and sediment movement modeling studies [4,5,[25][26][27], for a summary see [28]. For this location disposal of dredged material in a dredge disposal site, which is outside of the estuarine system, or the recharge of sandy beaches on Wild Cattle Island may be an appropriate option for managers.…”
Section: Discussionsupporting
confidence: 69%
“…For example, in the outer seaward Wild Cattle Channel the data indicate that the sediment has a marine rather than catchment derivation, with 7 Be activities equally low in dry and post wet conditions and less depleted δ 13 C. Wild Cattle Channel also had a similar REE composition to sediments from offshore of the Rodds Peninsula, a site chosen as indicative of longshore drift. Such a finding is supported by previous hydrodynamic and sediment movement modeling studies [4,5,[25][26][27], for a summary see [28]. For this location disposal of dredged material in a dredge disposal site, which is outside of the estuarine system, or the recharge of sandy beaches on Wild Cattle Island may be an appropriate option for managers.…”
Section: Discussionsupporting
confidence: 69%
“…Evaluation of the environmental effects derived from the outputs from the modeling of the sediments released from marine construction activities are facilitated by comparisons with the SSC, and sediment deposition rates under natural conditions for the study area. The sediment regime of the natural environment can be represented through SSC and sediment deposition rates realized from observations or from sediment background models which use similar methods to those of the present study (e.g., Reference [25]).…”
Section: Sediment Transport Computational Modulementioning
confidence: 99%
“…According to many researches aiming at the digital modelization of estuaries and the prediction of their behavior, it has been demonstrated that their functioning is complex in most estuaries of the world due to the action of many factors controlling the equilibrium in these environmental systems [1][2][3][4][5]. Indeed, the factors controlling the morphodynamics of estuaries and deltas are variable, including natural factors such as sea level change, swell and tide actions, storm event, fluvial hydrology, etc., and…”
Section: Introductionmentioning
confidence: 99%
“…The morphodynamic change concerns the estuary outlet, the main channel, and the intertidal plains [19,20,28]. In addition, the morphodynamic change in the estuary affects the morphology of neighboring littoral areas and, consequently, causes the shoreline fluctuation [3,[29][30][31]. Numerous works have analyzed the morphologic evolution of coastal systems through multi-temporal photographs [30,[32][33][34][35][36][37][38][39][40].This study is an attempt to provide elements to aid in understanding the Oum Er-Rbia coastal system's behavior by analyzing the estuarine morphodynamic evolution and comparing it with the evolution of the hydraulic facilities installed in the catchment area, as well as the shoreline changes observed in the neighboring marine beaches.represents less than 3% of the main watercourse, but its situation downstream makes its important as a zone sensible to hydrodynamic changes in both upstream and littoral areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation